Mass Diffusion in Process Metallurgy - Nurni, Viswanathan Neelakantan; Ballal, Bharath Nidambur; Seetharaman, Seshadri (Diffusion foundations and materials applications, 2015)
Diffusion phenomena are of great importance in materials processing wherein atomic, molecular or ionic species are distributed within a phase or among different phases. Though the phenomenological equation describing the diffusion phenomena including the bulk flow arising out of diffusion in fluid and the phenomena of Kirkendall shift in substitutional solids are the same, these processes are often treated independently. Some discussion on this aspect is presented in the theoretical aspects of diffusion. Owing to the complexity of atomic interactions, prediction of diffusion coefficients in condensed systems from first principles may not be that reliable; Experimental determination of diffusion coefficients is essential. In the second section, some novel experimental techniques developed recently to measure diffusion coefficients in the solid state as well as liquid systems including those in slags are described. In the last section, two case studies on application of diffusion phenomena in process metallurgy are presented emphasizing the importance of these in metallurgical processing.